The The Effects of Massage Therapy on a Patient with Migraines and Cervical Spondylosis: a Case Report - Rostron, RMT, Sarah (International Journal of Therapeutic Massage & Bodywork, 2021)
Background: Migraines involve moderate- to-severe neck and face pain that lasts four to 72 hours, and are followed by fatigue and stiffness. Migraines are treated using medications, massage therapy (MT), and non-pharmacological alternatives. Cervical spondylosis (CS) is characterized by degeneration of the intervertebral discs, neck pain, and involvement of soft tissues in the cervical area. CS is treated using medications and manual therapy, including MT. Objective: To determine the effects of MT on cervical range of motion and daily function in a patient with migraines and CS. Case Presentation: The patient was an active 56-year-old female diagnosed with migraines and CS. Initial evaluation included cervical range of motion (ROM), goniometry, reflexes, myotomes, dermatomes, local sensation testing and orthopedic tests. Assessment was followed by five MT treatments. Swedish massage, myofascial trigger point release, and proprioceptive neuromuscular facilitation (PNF) stretching were applied to the back, neck, head, and face. The Headache Disability Index (HDI) was administered on the initial and final visits to evaluate patient function. Cervical ROM was measured pre- and posttreatment using a universal goniometer. Treatment was conducted by a second-year MT student at the MacEwan Massage Therapy Teaching Clinic in Edmonton, Alberta. Results: All cervical ranges of motion improved. The Headache Disability Index score decreased, but was not considered significant. The patient reported decreased stiffness in the upper back and shoulders, reduced migraines, and better sleeping patterns after the MT intervention. Conclusion: MT was effective in increasing cervical ROM, but had no significant effect on daily function. Further research is warranted on effects of MT on CS and migraines.